Improvement Strategy for the Quality of the Equivalency Education Program (Package C) - Syamsul, Moh; Roesminingsih, Maria Veronica (Universitas Negeri Padang, 2024)
This study investigates the quality improvement strategy for the Equivalency Education Program Package C at PKBM Al-Islah Bakeong, Guluk-Guluk District, Sumenep Regency, Madura. The qualitative research method was employed, utilizing interviews, observations, and document analysis to gather comprehensive data. The findings indicate that the management of the Package C Equivalency Education Program at PKBM Al-Islah has not yet reached an advanced level of educational quality. This is evidenced by various supporting and hindering factors in both management and the teaching and learning methods used. Supporting factors include the commitment of the management team to develop an educated and skilled community. However, the program faces significant obstacles, such as low community awareness of PKBM's existence and function, limited facilities, and restricted business units managed by PKBM. Further challenges in improving the quality of education include societal indifference towards education's importance and insufficient support from the local government, both morally and materially. Most learners come from lower-middle-class backgrounds with limited economic resources, which affects their ability to provide necessary learning materials, thereby placing the burden on PKBM to supply and facilitate these needs. The quality improvement strategies implemented by PKBM Al-Islah include stimulating learning motivation, enhancing the provision of infrastructure, and gradually developing teaching methods. Despite these efforts, ongoing challenges highlight the need for greater community and government support to ensure the program's success and sustainability.